2002
DOI: 10.1074/jbc.m106457200
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin Scaffolding of the ERK Cascade Enhances Cytosolic ERK Activity but Inhibits ERK-mediated Transcription following Angiotensin AT1a Receptor Stimulation

Abstract: ␤-Arrestins are cytosolic proteins that mediate homologous desensitization of G protein-coupled receptors (GPCRs) by binding to agonist-occupied receptors and by uncoupling them from heterotrimeric G proteins. The recent finding that ␤-arrestins bind to some mitogen-activated protein (MAP) kinases has suggested that they might also function as scaffolds for GPCR-stimulated MAP kinase activation. To define the role of ␤-arrestins in the regulation of ERK MAP kinases, we examined the effect of ␤-arrestin overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
297
2
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 360 publications
(323 citation statements)
references
References 31 publications
20
297
2
4
Order By: Relevance
“…Arrestins work as scaffolds recruiting a number of components of several MAPK cascades to activated GPCRs, thereby mediating activation of the MAPK pathways. In particular, both non-visual arrestins have been shown to activate ERK [66,87,100]. Over-expression of arrestins potentiates arrestin-mediated ERK activation [100,101].…”
Section: Functional Significance Of Changes In Arrestin and Grk Exprementioning
confidence: 99%
See 1 more Smart Citation
“…Arrestins work as scaffolds recruiting a number of components of several MAPK cascades to activated GPCRs, thereby mediating activation of the MAPK pathways. In particular, both non-visual arrestins have been shown to activate ERK [66,87,100]. Over-expression of arrestins potentiates arrestin-mediated ERK activation [100,101].…”
Section: Functional Significance Of Changes In Arrestin and Grk Exprementioning
confidence: 99%
“…In particular, both non-visual arrestins have been shown to activate ERK [66,87,100]. Over-expression of arrestins potentiates arrestin-mediated ERK activation [100,101]. Conversely, reduction of the arrestin concentration by siRNAs inhibits ERK activation [3].…”
Section: Functional Significance Of Changes In Arrestin and Grk Exprementioning
confidence: 99%
“…This is as a signal transducer and adaptor which scaffolds a variety of signaling molecules, for example, Src family kinases (6 -8) and components of mitogen-activated protein kinase (MAPK) cascades, leading to their activation (8 -14). Such scaffolding and targeting of activated extracellular signal-regulated kinases (ERKs) to a cytoplasmic vesicular compartment has been demonstrated for angiotensin II type 1A (AT 1A ) (11,12), neurokinin 1 (8), proteinase-activated (9), and vasopressin 2 (V 2 ) receptors (13). Overexpression of ␤-arrestins enhances cytosolic ERK activation following stimulation of AT 1A or V 2 receptors (11)(12)(13).…”
mentioning
confidence: 99%
“…Such scaffolding and targeting of activated extracellular signal-regulated kinases (ERKs) to a cytoplasmic vesicular compartment has been demonstrated for angiotensin II type 1A (AT 1A ) (11,12), neurokinin 1 (8), proteinase-activated (9), and vasopressin 2 (V 2 ) receptors (13). Overexpression of ␤-arrestins enhances cytosolic ERK activation following stimulation of AT 1A or V 2 receptors (11)(12)(13). In addition, studies using the RNA interference (RNAi) technique have demonstrated that ␤-arrestin2 mediates G protein-independent ERK1/2 activation following AT 1A receptor stimulation (15), as well as that ␤-arrestin2 is required for CXCR4 chemokine receptor-mediated ERK1/2 and p38 activation (16).…”
mentioning
confidence: 99%
“…Clathrin-coated pits, where receptors, GIPC, GAIP, and G proteins could all meet, are important sites for the assembly of endocytosis and MAP-kinase signaling machineries (Luttrell et al, 1999). Indeed, ␤-arrestin2, which serves as a scaffold protein for GPCR endocytosis (Goodman et al, 1996) and GPCR-induced Erk activation (Tohgo et al, 2002), colocalized with GIPC in D 2 R-expressing cells stimulated by quinpirole (Supplementary Information; Figure 5). Thus, the GIPC and GAIP could take part in the GPCR-associated scaffold that connects both tightly related machineries.…”
Section: Discussionmentioning
confidence: 99%